Alpha-geminal dihydroxymethyl piperidine and pyrrolidine iminosugars: synthesis, conformational analysis, glycosidase inhibitory activity, and molecular docking studies - Pawar, Nitin J.; Parihar, Vijay Singh; Chavan, Sanjay T.; Joshi, Rakesh S.; Joshi, Pranaya V.; Sabharwal, Sushma G.; Puranik, Vedavati G.; Dhavale, Dilip D. (Journal of Organic Chemistry, 2012)
The Jocic-Reeve and Corey-Link type reaction of dichloromethyllithium with suitably protected 5-keto-hexofuranoses followed by treatment with sodium azide and sodium borohydride reduction gave 5-azido-5-hydroxylmethyl substituted hexofuranoses 7a-c with required geminal dihydroxymethyl group. Removal of protecting groups and converting the C-1 anomeric carbon into free hemiacetal followed by intramolecular reductive aminocyclization with in situ generated C5-amino functionality afforded corresponding 5C-dihydroxymethyl piperidine iminosugars 2a-c. Alternatively, removal of protecting groups in 7b and 7c and chopping of C1-anomeric carbon gave C2-aldehyde that on intramolecular reductive aminocyclization with CS-amino gave 4C-dihydroxyrnethyl pyrrolidine iminosugars 1b and 1c, respectively. On the basis of the H-1 NMR studies, the conformations of 2a/2b were assigned as C-4(1) and that of 2c as C-1(4). The glycosidase inhibitory activities of all five iminosugars were studied with various glycosidase enzymes and compared with natural o-g/uco-l-deoxynojirimycin (DNJ). All the five compounds were found to be potent inhibitors of rice alpha-glucosidase with K-i and IC50 values in the nanomolar concentration range. Iminosugars 2b and 1b were found to be more potent inhibitors than their parent iminosugar. These results were substantiated by in silico molecular docking studies.

Catechin-capped silver-doped titanium dioxide nanoparticle enhanced photocatalytic toxic dye degradation - Ghosh, Sougata; Imboon, Tanawat; Layek, Rashbihari; Salunke, Gayatri; Parihar, Vijay Singh; Khumphon, Jeerawan; Webster, Thomas J.; Sutar, Santosh; Kityakarn, Sutasinne; Issro, Chaisak; Khamboonrueang, Dusadee; Thongmee, Sirikanjana (Frontiers in Chemistry, 2025)
Doping-associated surface modification is a powerful strategy to enhance the photocatalytic potential of n-type semiconductor nanomaterials. Silver (Ag) is one of the most effective dopants that can result in the retardation of the electron hole recombination-generating Schottky barrier at the TiO2 interface with a simultaneous extension of absorption to the visible region. This work presents a study on the effect of catechin, a bioactive principle polyphenol compound found in various plants, on the synthesis, Ag-doping and stabilization of TiO2 nanoparticles (TiO2NPs). The nanoparticles were irregular in shape with sizes ranging from 19 to 30 nm. Ag-TiO2NPs were fabricated using TiO2 as a precursor and 1%, 3%, and 5% AgNO3 as a doping agent. The average particle size of 1%Ag-TiO2NPs, 3%Ag-TiO2NPs, and 5%Ag-TiO2NPs was 27.3 +/- 7.5 nm, 29.8 +/- 9.6 nm, and 25.0 +/- 9.0 nm, respectively. High-resolution transmission electron microscopy (HRTEM) showed lattice fringes with an interplanar spacing of 0.23 nm corresponding to the Ag (111) plane in addition to the presence of the anatase phase of TiO2. Fourier transform infrared (FTIR) spectra exhibited a broad peak around 400-800 cm-1 that was attributed to Ti-O-Ti stretching vibrations which was slightly shifted in Ag-TiO2NPs due to changes in the local bonding environment around Ti atoms caused by interactions with Ag. Catechin loading in the TiO2NPs and Ag-TiO2NPs was between 1.55 and 3.3 wt. %. TiO2NPs, 1%Ag-TiO2NPs, 3%Ag-TiO2NPs, and 5%Ag-TiO2NPs exhibited superior photocatalytic degradation of methylene blue dye up to 78%, 87%, 91%, and 92%, respectively, and RhB dye up to 92%, 94%, 97% and 99%, respectively, with a pseudo-first-order reaction kinetics. Furthermore, its recyclability was also demonstrated for three cycles. The simplicity of fabrication and superior photocatalytic performance of TiO2 demonstrated here make this green route advantageous for environmental applications to treat dye contaminated effluent as well as for numerous other applications.
Keywords: catechin; green synthesis; methylene blue dye; Photocatalysis; Rhodamine B; silver doping; titanium dioxide nanoparticles